Предмет: Алгебра, автор: belitka

Срочно нужна помощь помогите в течение 15 минут

Приложения:

Ответы

Автор ответа: eugeke
0
 frac{ frac{1}{a}- frac{1}{b-c} }{frac{1}{a}+frac{1}{b-c} } cdot(1- frac{b^2+c^2-a^2}{2bc}): frac{b-a-c}{abc},  npu  a=1,2;  b=0,5;  c=1,3

1.   frac{1}{a}- frac{1}{b-c} = frac{b-c-a}{a(b-c)}\\\
2.  frac{1}{a}+ frac{1}{b-c} =frac{b-c+a}{a(b-c)}\\\
3.   frac{b-c-a}{a(b-c)}cdot frac{a(b-c)}{b-c+a}=frac{b-c-a}{b-c+a}= frac{-a+b-c}{a+b-c} \\\
4.  (1- frac{b^2+c^2-a^2}{2bc})= frac{2bc-b^2-c^2+a^2}{2bc}= frac{-(b^2-2bc+c^2)+a^2}{2bc}=\\
= frac{a^2-(b-c)^2}{2bc}= frac{(a-b+c)(a+b-c)}{2bc} \\\


5.   frac{-a+b-c}{a+b-c} cdotfrac{(a-b+c)(a+b-c)}{2bc} = frac{(a-b+c)(-a+b-c)}{2bc}= frac{-(a-b+c)(a-b+c)}{2bc}=\\
=- frac{(a-b+c)^2}{2bc} \\\
6.  - frac{(a-b+c)^2}{2bc} cdot frac{abc}{b-a-c}=- frac{a(a-b+c)^2}{2(b-a-c)}= frac{a(a-b+c)^2}{2(a-b+c)}= frac{a(a-b+c)}{2}   \\\
frac{a(a-b+c)}{2},  npu  a=1,2;  b=0,5;  c=1,3\\
 frac{1,2cdot(1,2-0,5+1,3)}{2}= frac{1,2cdot2}{2}  =1,2
Похожие вопросы